EVALUATING A DANCE-RELATED ONGOING TRAINING PROCESS: ACTION RESEARCH IN FOCUS - Roberta Santos Azambuja dos Santos; Mariângela da Rosa Afonso; Verônica Gabriela Silva Piovani; Luciana Toaldo Gentilini Ávila (Journal of Physical Education)
ABSTRACT Ongoing training is a quite relevant theme in the education field. It allows teachers to develop their professional skills, seeking to solve everyday problems by means of acquired information or of information resulting from reflection with peers about pedagogical practice. Thus, the objective of this research was to assess the possibilities of an action research in ongoing training involving school dance with Physical Education teachers from the municipality of Bagé, Rio Grande do Sul, Brazil. The study had the participation of 26 teachers from the municipal network. The methodological proposal followed the different steps of action research, comprehending the identification of needs (step 1), action planning (step 2), action implementation (step 3), action description and monitoring (step 4) and action result evaluation (step 5). Action results suggested the appropriation of knowledge by the teachers, greater motivation toward the teaching practice in school, effective exchange among peers, and possibility of approaching dance in school. The study also revealed the importance of ongoing training, allowing the construction of new types of learning, with changes in the teachers' attitudes, knowledge and pedagogical practices.